Medicaid Managed Care and the Health Care Utilization of Foster Children. (15th March 2017) - Palmer, Makayla; Marton, James; Yelowitz, Aaron; Talbert, Jeffery
A recent trend in state Medicaid programs is the transition of vulnerable populations into Medicaid managed care (MMC) who were initially carved out of such coverage, such as foster children or those with disabilities. The purpose of this article is to evaluate the impact of the transition of foster children from fee-for-service Medicaid coverage to MMC coverage on outpatient health care utilization. There is very little empirical evidence on the impact of managed care on the health care utilization of foster children because of the recent timing of these transitions as well as challenges associated with finding data sets large enough to contain a sufficient number of foster children for such analysis. Using administrative Medicaid data from Kentucky, we use retrospective difference-in-differences analysis to compare the outpatient utilization of foster children transitioned to MMC in one region of the state with foster children in the rest of the state who remained in fee-for-service coverage. We find that the transition to MMC led to a 4 percentage point reduction in the probability of having any monthly outpatient utilization. We also estimate that MMC leads to a reduction in outpatient spending.